Character analysis of adaptations for tarsal pollen collection in the Bombyliidae (Insecta: Diptera): the benefits of putting your foot in your mouth - Neff, John L.; Simpson, Beryl B.; Evenhuis, Neal L.; Dieringer, Gregg (Zootaxa, 2003)
Using direct observations and analyses of gut contents, we document that pollen feeding is widespread among female bombyliid flies. Pollen feeding is typically indirect with the initial pollen acquisition accomplished by foretarsal stroking of the anthers. Observations of the foretarsi using light and scanning electron microscopy showed that the foretarsi bear modified setae that play a role in pollen collection. Across the family, we found considerable variation in the morphology and distribution of the foretarsal setae that appear to be more related to phylogeny than pollen host. The major patterns of foretarsal setal specialization are illustrated and discussed.